Depth perception: the need to report ocean biogeochemical rates as functions of temperature, not depth - Brewer, Peter G. (Philos Trans A Math Phys Eng Sci, 2017)
For over 50 years, ocean scientists have oddly represented ocean oxygen consumption rates as a function of depth but not temperature in most biogeochemical models. This unique tradition or tactic inhibits useful discussion of climate change impacts, where specific and fundamental temperature-dependent terms are required. Tracer-based determinations of oxygen consumption rates in the deep sea are nearly universally reported as a function of depth in spite of their well-known microbial basis. In recent work, we have shown that a carefully determined profile of oxygen consumption rates in the Sargasso Sea can be well represented by a classical Arrhenius function with an activation energy of 86.5 kJ mol(−1), leading to a Q(10) of 3.63. This indicates that for 2°C warming, we will have a 29% increase in ocean oxygen consumption rates, and for 3°C warming, a 47% increase, potentially leading to large-scale ocean hypoxia should a sufficient amount of organic matter be available to microbes. Here, we show that the same principles apply to a worldwide collation of tracer-based oxygen consumption rate data and that some 95% of ocean oxygen consumption is driven by temperature, not depth, and thus will have a strong climate dependence. The Arrhenius/Eyring equations are no simple panacea and they require a non-equilibrium steady state to exist. Where transient events are in progress, this stricture is not obeyed and we show one such possible example. This article is part of the themed issue ‘Ocean ventilation and deoxygenation in a warming world’.